Editorial - Oniwide, Oyetola (NIU Journal of Educational Research, 2025)
This edition of NIU Journal of Educational Research touches on Digitalized Citizenship Education, Open Education Systems, Multimodal Literacy in Higher Education, University Health Education and the Role of Academics in Democratic Movements. One of the papers, in this issue, reveals that the practice pattern of University Health Education students is either good or poor. Moreover. While the exercise behaviour, regular behaviour, health risk behaviour and life appreciation were statistically significantly different by gender, nutrition, health responsibility, social support and stress management were not statistically significantly different by gender. It is, therefore, suggested that the poor practice pattern of the students in healthy lifestyle indices can be improved through sensitization of the students by their lecturers on indices in which they reported poorly. Another paper also reveals that that when thoughtfully implemented, multimodal literacy can enhance student engagement, academic performance, and digital competence. However, infrastructural limitations and uneven faculty readiness remain key challenges. The paper therrfore, recommends increased investment in digital infrastructure, targeted faculty development, and the inclusion of structured digital literacy programmes within university curricula. On the whole, this issue of NIU Journal of Educational Research features many empirical and theoretical based articles which can be of great benefit to every reader.